Irony in the Bible : Between Subversion and Innovation - Häner, Tobias,; Miller, Virginia;,; Sharp, Carolyn J., (Biblical Interpretation Series ;, 2023)
It is generally agreed that there is significant irony in the Bible. However, to date no work has been published in biblical scholarship that on the one hand includes interpretations of both Hebrew Bible and New Testament writings under the perspective of irony, and on the other hand offers a panorama of the approaches to the different types and functions of irony in biblical texts. The following volume: (1) reevaluates scholarly definitions of irony and the use of the term in biblical research; (2) builds on existing methods of interpretation of ironic texts; (3) offers judicious analyses of methodological approaches to irony in the Bible; and (4) develops fresh insights into biblical passages.